Scenarios of climate change and natural resource development: Complexity and uncertainty in the Nechako Watershed. (1st April 2020) - Picketts, Ian M.; Déry, Stephen J.; Parkes, Margot W.; Sharma, Aseem R.; Matthews, Carling A.
Abstract : Climate change and resource development interact to have significant impacts on both natural and human systems within watersheds. It is, however, difficult to conceptualize and communicate these intersections, as climate change and resource development are each independently uncertain and complex. We facilitated a process whereby stakeholders created plausible future scenarios for the Nechako Watershed in British Columbia, Canada. This region is reliant upon, and has been significantly affected by, many types of resource exploitation. During a full‐day workshop, 32 stakeholders created scenarios for 2050 envisioning high and low levels of both resource development and climate change. The high and low levels of climate change were based on downscaled projections from global emissions scenarios, and the resource development levels were determined at the beginning of the workshop by the participants. The exercise was educational, and motivated stakeholders to conceptualize plausible future changes and their impacts, and the outcomes should motivate stakeholders to work towards realizing a more desired future. All scenarios (even low‐low) were deemed to have significant negative impacts, suggesting that the Nechako Watershed is in a vulnerable state. The complexity of the exercise suggests that more capacity building may be necessary. Key Messages: It is important to consider the interrelationships of resource development and climate change on watersheds. Stakeholder‐created scenarios can help determine plausible futures for a region and help people to work towards realizing a desired outcome. The Nechako Watershed has already been significantly affected by both resource development and climate change, therefore active management is necessary. Les scénarios de changements climatiques et le développement des ressources naturelles : complexité et incertitude dans le bassin hydrographique de la Nechako: Les changements climatiques et le développement des ressources interagissent et ils peuvent avoir des répercussions importantes sur les systèmes humains et naturels dans les bassins hydrographiques. Il est toutefois difficile de conceptualiser et de communiquer ces interactions parce que les changements climatiques et le développement des ressources sont tous les deux à la fois incertains et complexes. Nous avons mis en place un processus dans lequel les intervenants du milieu ont créé des scénarios futurs plausibles pour le bassin hydrographique de la Nechako en Colombie‐Britannique, au Canada. Cette région dépend de nombreux types d'exploitations des ressources et celle‐ci a été grandement affectée par ces activités économiques. Durant un atelier d'une journée, 32 intervenants ont créé des scénarios pour l'année 2050 envisageant des niveaux faibles et élevés de développement des ressources et de changements climatiques. Les niveaux faibles et élevés de changements climatiques étaient fondés sur des projections à échelle réduite de scénarios d'émissions mondiales et les niveaux de développement des ressources ont été déterminés au début de l'atelier par les participants. L'exercice était éducatif et il a motivé les intervenants à conceptualiser des changements futurs plausibles ainsi que leurs répercussions et les résultats devraient motiver les intervenants à travailler pour un futur davantage souhaitable. Tous les scénarios (même les faibles‐faibles) étaient considérés comme ayant des répercussions négatives importantes, suggérant l'idée que le bassin hydrographique de la Nechako soit dans un état de vulnérabilité. La complexité de l'exercice nous conduit à conclure qu'une stratégie de sensibilitaion plus importante est probablement requise.